تصميم برنامج حاسوبي عبر شبكة الإنترنت لتعليم اللغة العربية للمتخصصين في السياحة: طلبة كلية مارا للتقنية نموذجًا - Mohammad Taufiq bin Abdul Ghani (al-Jami'ah al-Islamiyah al-'Alamiyah, 2016)
The purpose of this study is to help students to learn Arabic for tourism purposes by designing a special website to teach them the language. The study was conducted using the descriptive and analytical methodologies. A special website “www.arabicfortourism.com” was designed by using Joomla as a platform for website development along with the implementation of the ADDIE instructional model. The website was designed based on students' needs, opinions, and suggestions which were evaluated based on the participants of this study, which consist of tourism students. The participants of the study were selected using the purposive sampling method. Two experts in Computer Assisted Instruction (CAI) and 70 level-one tourism students from MARA Poly-Tech College (KPTM) were chosen in the need analysis phase, and 40 students were selected to participate in the evaluation phase of the study which was carried out during the first semester of the 2015/2016 academic year. The study found that the majority of the students were positive about learning the Arabic language for tourism purposes through the website which increases the students' desire, motivates them to learn Arabic and gives them opportunities to practise self-learning.